Decreased IGF1R attenuates senescence and improves function in pancreatic β-cells - Iwasaki, Kanako; Lalani, Benjamin; Kahng, Jiho; Carapeto, Priscila; Sanjines, Stephanie; Hela, Francesko; Abarca, Cristian; Tsuji, Tadataka; Darcy, Justin; Bartke, Andrzej; Tseng, Yu-Hua; Kulkarni, Rohit N.; et al. (Frontiers in Endocrinology, 2023)
The enhanced β-cell senescence that accompanies insulin resistance and aging contributes to cellular dysfunction and loss of transcriptional identity leading to Type 2 Diabetes (T2D). While senescence is among the twelve recognized hallmarks of aging, its relation to other hallmarks including altered nutrient sensing (Insulin/IGF1 pathway) in β-cells is not fully understood. We previously reported that increased expression of IGF1R in mouse and human β-cells is a marker of older β-cells; however, its contribution to age-related dysfunction and cellular senescence remains to be determined. In this study, we explored the direct role of IGF1R in β-cell function and senescence using two independent mouse models with decreased IGF1/IGF1R signaling a) Ames Dwarf mice (Dwarf +/+), which lack growth hormone and therefore have reduced circulating levels of IGF1, and b) inducible β-cells specific IGF1R knockdown (βIgf1rKD) mice. Compared to Dwarf+/- mice, Dwarf+/+ mice had lower body and pancreas weight, lower circulating IGF1 and insulin levels, and lower IGF1R and p21Cip1 protein expression in β-cells suggesting suppression of senescence. Adult βIgf1rKD mice showed improved glucose clearance and glucose-induced insulin secretion, accompanied by decreased p21Cip1 protein expression in β-cells. RNASeq of islets isolated from these βIgf1rKD mice revealed restoration of 3 signaling pathways known to be downregulated by aging: sulfide oxidation, autophagy, and mTOR signaling. Additionally, deletion of IGF1R in mouse β-cells increased transcription of genes important for maintaining β-cell identity and function, such as Mafa, Nkx6.1, and G6pc2, while decreasing senescence-related genes, such as Cdkn2a, Il1b, Mdk, Lsamp, Lamc1 and Serpine 1. Decreased senescence and improved insulin-secretory function of β-cells were also evident when the βIgf1rKD mice were fed a high-fat diet (HFD, 60% kcal from fat, for 5 weeks). These results suggest that IGF1R signaling plays a causal role in aging-induced β-cell dysfunction. Our data also demonstrate a relationship between decreased IGF1R signaling and suppressed cellular senescence in pancreatic β-cells. Future studies can further our understanding of the interaction between senescence and aging, developing interventions that restore β-cell function and identity therefore preventing the progression to T2D.